Application of nuclear magnetic resonance in medicine and its influence on the quality of life and work environment - Popović, Kristina D.; Korica, Sanja Lj. (Vojnotehnički glasnik / Military Technical Courier, 2016)
This work describes the application of nuclear magnetic resonance (NMR) in medicine and its influence on the work and life environment. Nuclear magnetic resonance, a powerful research tool, is based on the physical principle that cores of certain atoms (in this case hydrogen) can absorb or emit radiofrequency waves when placed in a magnetic field. This method is used for making high quality section pictures of the inside of the human body; in addition, it shows high sensitivity in revealing cancer, its position and its relation to the surrounding tissue. It is characterised by the use of non-ionizing radiation and a strong magnetic field, and, as explored by now, it does not have harmful effects on the human body.Therefore, it is completely noninvasive, comfortable and safe for patients as well for medical workers.